An analysis of load-carrying fillet welds using boundary element method - Bian, Chengmei. (2009)
The present work describes the effect of weld size and degree of weld penetration on the fatigue behaviour of load-carrying fillet welded joints. The Boundary Element Method (BEM) is employed in the analysis of such welded joints. Two techniques are used to estimate the stress intensity factors at the weld root and toe. They are the traction-singular Quarter-Point element method (Q-P) and the stress extrapolation method using Hypersingular Boundary Integral Equations (HBIE). In the first method, the stress intensity factor can be evaluated in a simple way by using quarter-point elements at the crack tip. In the second method, the boundary stresses along and ahead of the crack surface are calculated accurately using HBIE, which are then used to estimate the stress intensity factors for the cracks. Both methods yield accurate values of stress intensity factors which are not sensitive to element size, and their percentage difference is around 1.5%. Because HBIE costs more computer time and space, it is decided to use only the Q-P element method to estimate the stress intensity factors in the fatigue crack propagation analysis.